Prevalence of Musculoskeletal Symptoms of the Hand Among Dental Students - Sánchez Marín EOR, AEGD, M. en C., Carlos Gonzalo (2018)
Introduction: Musculoskeletal symptoms of the upper extremities are common among dental workers due to exposure to risk factors including repetition, forceful exertions of the hand, and awkward wrist postures.  As dental students learn new skills and procedures during dental school, they experience a gradually increasing exposure to these risk factors. The purpose of this study was to determine the prevalence of hand and wrist musculoskeletal symptoms (MSS) among dental students of the University of Iowa. Methods: Thirty-five first year students and thirty-nine fourth year students (N=74) were asked to complete two questionnaires. Results: The prevalence of moderate/severe MSS of the dominant hand such as numbness, tingling and soreness among first year students was 0, 6 and 20% respectively compared to 18, 15 and 36% of the fourth year students. Conclusions: In this relatively small sample, MSS of the dominant hand were more common among fourth year dental students when compared to first year students.